Synthesis and Properties of Segmented Polyurethanes with Triptycene Units in the Soft Segment. Issue 11 (9th April 2015) - Chang, Zhengmian; Fahs, Gregory B.; Hudson, Amanda G.; Orler, E. Bruce; Moore, Robert B.; Wilkes, Garth L.; Turner, S. Richard
<x xml:space="preserve">Abstract</x> Segmented polyurethanes based on poly(tetramethylene glycol) soft segments (SS) containing aromatic units are synthesized. Hydroquinone bis(2‐hydroxyethyl) ether and 4, 4′‐methylenebis(phenyl isocyanate) are used as the chain extender and the diisocyanate, respectively. Effects of incorporation of hydroquinone (HQ) and triptycene hydroquinone into the soft segments on the morphology and properties of the undeformed segmented polyurethanes are investigated. Differential scanning calorimetry and dynamic mechanical analysis indicate that the incorporation of triptycene units leads to an increased glass transition temperature (Tg) and an elimination of the crystallization of soft segments. The tensile analysis shows there is no strain hardening for the polymer films with triptycene‐containing soft segments. Wide‐angle x‐ray diffraction demonstrates that the absence of strain hardening in triptycene‐containing segmented polyurethane likely arises from the suppressed strain induced crystallization. In contrast, the less bulky HQ units show little effect on either thermally or strain induced crystallization of the soft segments. Morphology studies, including small angle x‐ray scattering on the compression molded films and atomic force microscopy on the solvent cast film, reveal that polyurethanes with HQ and triptycene containing soft segments maintain distinct microphase separated morphology.